Antimicrobial potential of the injectable platelet rich fibrin : a scoping review - Carvalho, Dylan de (2024)
Purpose: The purpose was to perform a scoping review on the antimicrobial effects of the injectable platelet rich fibrin. Materials and Methods: A literature pursuit was conducted on PubMed and Scopus electronic database, within English studies published in the last 15 years. The following keywords were used: “antimicrobial” OR “antibiofilm” OR “antibacterial” AND “platelet rich fibrin” OR “PRF” OR “injectable platelet rich fibrin” OR “i-PRF” OR “injectable PRF” AND “bacteria” OR “Periodontal pathogen” OR “Aggregatibacter actinomycetemcomitans” OR “Prevotella intermedia” OR “Porphyromonas gingivalis”. Results: The literature search identified a total of 720 articles although eleven studies were selected for this review. The findings from the selected studies showed inhibitory effect of the injectable platelet rich fibrin against biofilm-growing of around 40 and 50%. A peak of the inhibitory effect was reported after 12 h incubation in the medium containing Aggregatibacter actinomycetemcomitans. The studies validate the hypothesis on the i-PRF content of leukocytes on the inhibition of pathogenic bacteria. Furthermore, the association between an injectable PRF and traditional antimicrobials also revealed a high localized antimicrobial activity. Conclusions: Injectable platelet rich fibrin reveals a significant inhibitory effect against a variety of oral microbial species, that become a noteworthy potential to decrease the risks of further infection in wound healing.